2009
DOI: 10.1007/s11605-009-0853-3
|View full text |Cite
|
Sign up to set email alerts
|

National Trends and Outcomes for the Surgical Therapy of Ileocolonic Crohn’s Disease: A Population-Based Analysis of Laparoscopic vs. Open Approaches

Abstract: A variety of patient- and system-related factors influence the utilization of laparoscopy in Crohn's disease. Laparoscopic resection is associated with excellent short-term outcomes compared to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 27 publications
2
53
0
2
Order By: Relevance
“…This bias may be associated with preselection by the surgeons with regard to clinical conditions and was corresponding to current guideline recommendations as well as the results of other study groups that investigated retrospective cohorts of patients with Crohn's disease. 7,8 The main key point of laparoscopic surgery is the often very young age of the patients and the risk of surgical recurrence because of the chronic nature of the disease. 9,10 In addition, it is presumed that a laparoscopic access allows faster recovery and return to work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias may be associated with preselection by the surgeons with regard to clinical conditions and was corresponding to current guideline recommendations as well as the results of other study groups that investigated retrospective cohorts of patients with Crohn's disease. 7,8 The main key point of laparoscopic surgery is the often very young age of the patients and the risk of surgical recurrence because of the chronic nature of the disease. 9,10 In addition, it is presumed that a laparoscopic access allows faster recovery and return to work.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In one study, of the total 1,917 patients, the patients of open surgery group had median age of 42 years, whereas it was 37 years in the laparoscopic group. 7 Similar results were obtained by the second study in which 50,000 patients were included with abdominal surgery due to Crohn's disease in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently in a prospective study, Goyer et al [21] of complications, shorter length of stay, and reduced mortality. Open operations were more likely performed for patients in fistulizing disease and when an ostomy was necessary [22] . This indicates that there is still a need for conventional surgery in patients with Crohn's disease, especially for those with complicated disease and repetitive surgery.…”
Section: Laparoscopic Surgery For Crohn's Diseasementioning
confidence: 99%
“…A review published by Lesperance in 2009 found that minimally invasive techniques were used in only 6 % of the 50,000 interventions performed in the United States in 2000-2004 for Crohn's disease, and this figure showed little or no change over the 5-year period examined by the authors. However, these data were extracted from hospital discharge forms examined at the national level, and they contrast with those from surgical referral centers, where the rate of laparoscopic procedures is much higher [116].…”
Section: Laparoscopy and Crohn's Diseasementioning
confidence: 99%